Clinical characteristic of hemolytic-uremic syndrome in children of Orenburg region - E. V. Gunkova; I. V. Zorin; A. A. Vyalkova (Лечащий Врач)
Hemolytic-uremic syndrome (HUS) refers to primary thrombotic microangiopathy in whose pathogenesis, the main role belongs to damage to the endothelial lining of glomerular capillaries, hemolysis, activation and consumption of platelets with subsequent coagulation primarily with renal vessels. HUS remains a major cause of childhood AKI. In the age aspect GUS more often develops in children from 1 year to 5 years.